ON THE SIGNIFICANCE OF THE “ACADEMIC WRITING” COMPONENT IN THE TEXT OF THE OFFICIAL REVIEWS ON PHD THESES - Edita N. Merkulova (Высшее образование в России, 2016)
Abstract. The article raises the problem of the quality of academic writing in scholarly texts. For the purpose of defining the role and significance given to the academic writing aspect in scholarly texts, the author analyses a number of official reports on recently defended theses written by formally appointed reviewers. The article reveals that the reviewers’ comments on the quality of academic writing are of random character, and they mainly deal with stylistic issues. They are given little weight (if any) in the general assessment matrix. The reason for the situation could be the absence of universally accepted standards of academic writing. The Russian academic discourse needs profound research of its linguistic foundations, so that conventions of Russian academic writing could be developed. It will ultimately improve the quality of academic writing.